2020
DOI: 10.1016/j.apal.2020.102790
|View full text |Cite
|
Sign up to set email alerts
|

Bilattice logic of epistemic actions and knowledge

Abstract: Baltag, Moss, and Solecki proposed an expansion of classical modal logic, called logic of epistemic actions and knowledge (EAK), in which one can reason about knowledge and change of knowledge. Kurz and Palmigiano showed how duality theory provides a flexible framework for modelling such epistemic changes, allowing one to develop dynamic epistemic logics on a weaker propositional basis than classical logic (for example an intuitionistic basis). In this paper we show how the techniques of Kurz and Palmigiano ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…There are many extensions of other logics with public announcement that also involve reduction axioms for such announcements, such as intuitionistic PAL [10], bilattice PAL [16], Lukasiewicz PAL [5], and variations/extensions of action model logic like bilattice logic of epistemic actions and knowledge [1]. We can try to develop calculi for these logics with the steps similar to those for PAL.…”
Section: Corollary 16mentioning
confidence: 99%
“…There are many extensions of other logics with public announcement that also involve reduction axioms for such announcements, such as intuitionistic PAL [10], bilattice PAL [16], Lukasiewicz PAL [5], and variations/extensions of action model logic like bilattice logic of epistemic actions and knowledge [1]. We can try to develop calculi for these logics with the steps similar to those for PAL.…”
Section: Corollary 16mentioning
confidence: 99%
“…Parallel to this, the better knowledge or education acquired about the pandemic, the better stimulation toward prevention commitment (Bakhtiari et al , 2020; Gambhir et al , 2016; Nemati et al , 2020; Rahman et al , 2020). Meanwhile, many researchers found that the attitude of knowledgeable individuals on viral transmission modes and measures of prevention differ notably in comparison to unaware people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prevention behavior is a significant protective factor against COVID-19 epidemic infection. Rigorous preventive actions, articulated by preserving personal hygiene, frequent hand washing (Andualem and Sisay, 2017; Bakhtiari et al , 2020), practicing social distancing by refraining close human interaction, as well as quarantines adherence, could significantly help the county to overcome the health crisis and curb the rapid spread of COVID-19 (Khose et al , 2020; Seidel et al , 2020). The scope of perceived risk is widely related to people’s preventive behavior, but not necessarily pertinent to the actual level of risk (Betsch et al , 2020; Gardner et al , 2016; Quinn et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It improves students' thinking skills and cooperation in solving problems (Guo et al, 2020;Masrifah et al, 2020). Students' problem-solving abilities provide knowledge of the consequences of what students know (predict) (Bakhtiari et al, 2020). This ability will ultimately improve students' conceptual understanding (Kollmer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%